65 Frequential, temporal, and spatial analysis of cpr training in healthcare professionals. (17th November 2016) - Aitken, D; Chang, T; Stenfors-Hayes, T; MacKinnon, RJ
Abstract : The aim is; to understand frequency and timing of CPR training and to explore differences in training between cohorts of healthcare professionals. This should establish how to target CPR training for maximum effectiveness and sustain high quality CPR. A convenience sample of healthcare professionals was recruited from a UK children's hospital. Inclusion criteria was a current certification in basic life support. Participants were given unlimited access to infant CPR manikins and feedback devices over 6 months in their clinical areas. 1 A leaderboard was updated every 4 weeks with scores. A randomly generated number was allocated to each participant to track their progress. 2 The date and time for each training session was collected to investigate usage and popular training times. Demographics were recorded so comparisons could be made between speciality areas, and professions. Anticipated: Of the 90 participants, 75% returned to the manikins for training. 1000 uses of the manikins were recorded; the mean average was 11 uses (IQR 1.00 – 12.00), this increases CPR training to 2200% from once a year. The median was 5.00 and increases training 10x. 80% of training sessions were completed between 8am and 8pm and the most popular time was 1– 3 pm. However, this did not extend to all therefore, provision of training should be 24/7. Nurses trained the most, Doctors and ODPs contributed the approximately the same. This training has the advantage of not creating an additional time demand, and could be cheaper than traditional training as it negates costs of a CPR trainer and backfill of staff. Therefore, this training could improve patient outcomes, for the same time commitment, likely at a lower cost. 2, 3 This team will continue to expand this alternative CPR training with the aim of improving health outcomes of cardiac arrest patients across the world. References: Laerdal Inc., CPR scoring explained 2013 [Online]. Available: http://www.laerdal.com/downloads/f2729/Scoring_CPR_November_v2.pdf. [Accessed 10 ?September 2014]. RJ MacKinnon, R Stoeter, C Doherty, C Fullwood, A Cheng, V Nadkarni, T Stenfors-Hayes and T Chang. Self-motivated learning with gamification improves infant CPR performance, a randomised controlled trial. BMJ Simulation and Technology Enhanced Learning 2015. S Wallace, B Abella, L Becker. Quantifying the effect of cardiopulmonary resuscitation quality on cardiac arrest outcome: a systematic review and meta-analysis. Circ Cardiovasc Qual Outcomes 2013;6 :148–156.